Board Governance and Debt Cost: Evidence from technology companies listed on the Indonesian capital market - Natasha Cindy Widarmawan; Bram Hadianto (Politeknik Ganesha Medan, 2025)
Debt cost is critical in strategic corporate decision-making, particularly for creditors and investors prioritizing fund recovery assurance. At the same time, top management must mitigate financial risks by establishing an optimal financing structure. This investigation aims to inspect the determinants of the cost of debt. According to the governance mechanism, one of the determinants is the supervisory board, which is quantifiable through the total number of people in this position and its independence. Furthermore, this investigation uses a quantitative design to verify the hypotheses, the saturated sampling method to select the Indonesian capital market technology companies between 2018 and 2023, the regression model with pooling data estimated by ordinary least squares (OLS), and the t-statistic to examine the hypotheses, and the generalized method of moments (GMM) to check the robustness of pooling data. Based on the estimation, both GMM and OLS provide an equal tendency, making the data robust. Overall, the size of the supervisory board has a positive influence on the cost of debt, but its independence has a negative one. Based on these circumstances, technology companies should establish a small supervisory board to reduce debt costs and consider additional outside supervisory boards to further decrease this cost.